The Influence of Chronotype and Grit on Lifestyle and Physical Activity - Melody F. Allee; Sarah E. Anderson; Myra J. Bloom; Scarlet R. Jost; Donald P. Keating III; Andrew S.I.D. Lang; Nancy V. Mankin; Zachary W. Mast; Philip P. Nelson; Esther M. Spear; Enrique F. Valderrama (The Ohio State University Libraries, 2020)
Background:  The chronotype of a person refers to an individual's natural sleep-wake cycle and whether that individual prefers morning or evening activities, and grit is an individual's perseverance and passion for long-term goals. Aim: The purpose of this study was to investigate the relationship between grit, chronotype, physical activity, and leading a healthy lifestyle in college-age students. Methods:  Health and fitness data (i.e., chronotype, grit, lifestyle assessment score, and daily steps) from 431 first-semester university students at a private college were collected and analyzed.  Results: This study found that grit and chronotype both have significant correlations with living a healthy lifestyle and with physical activity. Grit more accurately predicts a person's lifestyle (β = -13.712, r = 0.39, p < 0.0001) while chronotype more accurately predicts the physical activity, or steps, of a person (β = 66.48, r = .19, p = .0001). Chronotype can also accurately predict the grit of a person (r = .25, p < .0001), and it was found that morning people tend to have more grit. Conclusions:  This study concluded that grit, chronotype, steps, and a healthy lifestyle are all significantly correlated with each other. Knowing the relationship between endogenous chronotype, grit, and living a physically active and healthy lifestyle can help inform policy decisions related to the goal of strengthening an institution's inclusive and healthy academic community.